Identity, Motivation And Investment For Target Learners (Texas Journal of Philology, Culture and History, 2024)
The current research examines how identity, investment, and motivation relate to [a particular learner group, such as young learners in a bilingual setting or adult immigrant learners]. We investigate the ways in which cultural background, past learning experiences, and social context affect learners' selfperceptions in regard to the target language, their belief in the importance of learning, and their will to keep going. We determine the main determinants of learning success in this particular demographic by employing a [Methodology, e.g., mixed-methods approach combining quantitative surveys and qualitative interviews]. Our results provide [briefly summarize key findings] and useful suggestions for teachers who are working with [Specific Learner Group] to improve language acquisition.